A high temperature resistant, oven resistant, microwave resistant PET material and preparation method thereof

By using PET materials prepared by modified isosorbate and furandicarboxylic acid, the problems of existing PET materials deformation and insufficient tensile strength under high temperature environments are solved, and the effects of high temperature resistance and high tensile strength are achieved, which are suitable for high temperature heating scenarios.

CN118373975BActive Publication Date: 2025-03-18YANTAI RISHENG PACKAGE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410631366.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-21
Publication Date
2025-03-18
Estimated Expiration
2044-05-21

AI Technical Summary

Technical Problem

Existing PET materials are prone to deform under high temperature environments, which limits their application, and their tensile strength is insufficient, making it difficult to meet the needs of high temperature and high tensile strength.

Method used

PET materials are prepared by using terephthalic acid, ethylene glycol, nucleation agent, crystallization promoter, modified isosorbate, modified furandicarboxylic acid, catalyst and antioxidant as raw materials. By modifying modified isosorbate and furandicarboxylic acid, the high temperature resistance and tensile strength of the material are improved.

Benefits of technology

It realizes the durability and high tensile strength of PET materials in high temperature environments. It is suitable for high-temperature heating scenarios such as microwave ovens or ovens, extending the service life of the materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a high temperature resistant, oven resistant, microwave resistant PET material and a preparation method thereof. The PET material comprises the following raw materials by weight: 54-58 parts of terephthalic acid, 23-27 parts of ethylene glycol, 1.2-1.8 parts of nucleating agent, 4-6 parts of crystallization promoter, 17-21 parts of modified isosorbide, 10-14 parts of modified furandicarboxylic acid, 0.5-1 parts of catalyst, and 0.2-0.6 parts of antioxidant. The high temperature resistant, oven resistant, microwave resistant PET material provided by the present invention has the advantages of good high temperature resistance and high tensile strength, and can be used in high temperature environments such as ovens and microwave ovens for heating without deformation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of PET materials, and in particular to a high-temperature, oven-resistant, microwave-resistant PET material and a preparation method thereof. Background Art

[0002] Polyethylene terephthalate (PET) is a commonly used material obtained by polycondensation of terephthalic acid and ethylene glycol. The long-term use temperature of PET material can reach 60-70°C, but it may deform under high temperatures in microwave ovens or ovens, which limits its application. The crystallinity and high temperature resistance of PET materials can be improved by adding nucleating agents and crystallization promoters, but in addition, the addition of other comonomers during the polymerization reaction can also improve the high temperature resistance of PET materials.

[0003] Isosorbide is a compound containing dihydroxyl groups, which can react with the carboxyl group of terephthalic acid to participate in the polycondensation reaction. The rigid ring in the isosorbide structure improves the heat resistance of the copolymer, but the rigid ring has a large steric hindrance, resulting in poor reactivity of the hydroxyl group connected to it, making the molecular chain of the generated copolymer shorter, thereby reducing the tensile strength. In addition, furandicarboxylic acid is an aromatic compound containing dicarboxyl groups, which can react with the hydroxyl group of ethylene glycol to participate in the polycondensation reaction. The rigid ring of furandicarboxylic acid can improve the high temperature resistance of the copolymer material and can slightly increase the tensile strength of the material, but the degree of improvement in tensile strength is limited.

[0004] The paper "Synthesis and Performance Study of Isosorbide Modified PET Copolyester" published in the journal "Synthesis Technology and Application" uses isosorbide to copolymerize with terephthalic acid and ethylene glycol to improve the high temperature resistance of the copolymer, but it does not solve the problem of short copolymer molecular chains, which reduces tensile strength. The paper "Synthesis and Performance Study of Furandicarboxylic Acid Modified PET" published in the journal "Polyester Industry" uses furandicarboxylic acid to copolymerize with terephthalic acid and ethylene glycol to improve the heat resistance of the copolymer and slightly increase the tensile strength, but the degree of improvement in tensile strength is limited.

[0005] Therefore, there is an urgent need for a PET material with good high temperature resistance and high tensile strength in the market. Summary of the invention

[0006] In view of the problems existing in the prior art, the object of the present invention is to provide a high temperature resistant, oven resistant and microwave resistant PET material and a preparation method thereof. The PET material of the present invention is prepared from terephthalic acid, ethylene glycol, a nucleating agent, a crystallization accelerator, modified isosorbide, modified furandicarboxylic acid, a catalyst and an antioxidant as raw materials, has the advantages of good high temperature resistance and high tensile strength, and is suitable for high temperature heating scenarios such as microwave ovens or ovens.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] On the one hand, the present invention provides a high-temperature, oven-resistant, microwave-resistant PET material, which comprises the following raw materials in parts by weight: 54-58 parts of terephthalic acid, 23-27 parts of ethylene glycol, 1.2-1.8 parts of a nucleating agent, 4-6 parts of a crystallization accelerator, 17-21 parts of modified isosorbide, 10-14 parts of modified furandicarboxylic acid, 0.5-1 parts of a catalyst, and 0.2-0.6 parts of an antioxidant.

[0009] In some embodiments of the present invention, the nucleating agent is a mixture of sodium o-chlorobenzoate and nano titanium dioxide.

[0010] Preferably, the mass ratio of the sodium o-chlorobenzoate to nano-titanium dioxide is (0.2-5):1.

[0011] Nucleating agents can improve the degree of crystallization of PET materials, thereby improving their high temperature resistance. Sodium o-chlorobenzoate is an organic small molecule nucleating agent, and its mechanism is ion clustering induced nucleation. Sodium o-chlorobenzoate can undergo sequence exchange reaction with PET to generate ion-terminated PET molecular chains, thereby accelerating crystallization; nano-titanium dioxide is an inorganic nucleating agent, which provides crystal nuclei in PET materials through the mechanism of heterogeneous nucleation, so that PET materials are transformed from homogeneous nucleation to heterogeneous nucleation, thereby increasing the nucleation rate. Using a mixture of sodium o-chlorobenzoate and nano-titanium dioxide as a nucleating agent can improve the nucleation effect through the synergistic effect of different mechanisms, thereby improving the high temperature resistance of PET materials.

[0012] The present invention does not impose any special restrictions on the source of the nano titanium dioxide, which can be purchased from commercial sources, including but not limited to the nano titanium dioxide purchased from Ningbo Luofei Nanotechnology Co., Ltd.

[0013] In some embodiments of the present invention, the crystallization promoter is polyethylene glycol or polytetramethylene glycol.

[0014] Polyethylene glycol and polytetramethylene glycol can improve the activity of polymer chain segments, thereby facilitating the crystallization of PET and making the crystallization more perfect.

[0015] The present invention does not impose any special restrictions on the sources of the polyethylene glycol and polytetramethylene ether glycol, which can be purchased commercially, including but not limited to the polyethylene glycol purchased from Shanghai Donghui Chemical Technology Co., Ltd., and including but not limited to the polytetramethylene ether glycol purchased from Jining Huakai Resin Co., Ltd.

[0016] In some embodiments of the present invention, the method for preparing modified isosorbide comprises the following steps:

[0017] Add p-toluenesulfonic acid, isosorbide and 3-hydroxypropionic acid to toluene in sequence, stir for 13-18 minutes, reflux at 110-115° C. for 5-6 hours, separate by column chromatography, and obtain modified isosorbide.

[0018] PET material is obtained by polycondensation after esterification of terephthalic acid and ethylene glycol. Isosorbide also contains two hydroxyl groups in its structure, which can react with the carboxyl group of terephthalic acid to participate in the polycondensation reaction. The rigid ring in the isosorbide structure can improve the high temperature resistance of the PET material, but the steric hindrance of the rigid ring is relatively large, resulting in poor reactivity of the hydroxyl group directly connected to the ring, making the molecular chain of the generated copolymer shorter, thereby reducing the tensile strength of the PET material. The applicant modified isosorbide by using 3-hydroxypropionic acid. Under the catalytic action of p-toluenesulfonic acid, the carboxyl group in 3-hydroxypropionic acid will undergo esterification reaction with the hydroxyl group in isosorbide, and the 3-hydroxypropionic acid structure also contains a hydroxyl group. Due to the introduction of a molecular chain in the esterification reaction, the distance between the new hydroxyl group and the rigid ring is relatively far, thereby improving the reactivity of the hydroxyl group, making the molecular chain of the generated polymer longer, thereby improving the tensile strength of the PET material.

[0019] In some embodiments of the present invention, the mass ratio of isosorbide to 3-hydroxypropionic acid is 1:(0.6-0.9).

[0020] Preferably, the mass ratio of isosorbide to 3-hydroxypropionic acid is 1:0.78.

[0021] The applicant selected isosorbide and 3-hydroxypropionic acid in a specific mass ratio to improve the hydroxyl reaction performance of the modified isosorbide, increase the length of the copolymer molecular chain, and thus improve the tensile strength of the PET material.

[0022] In some embodiments of the present invention, the method for preparing the modified furandicarboxylic acid comprises the following steps:

[0023] Aluminum trichloride and furandicarboxylic acid are added to dichloromethane, stirred for 12-15 minutes, acetic anhydride is added, reacted at a temperature of 21-26° C. for 7-8 hours, and separated by column chromatography to obtain modified furandicarboxylic acid.

[0024] The structure of furandicarboxylic acid contains two carboxyl groups, which can react with the hydroxyl group in the ethylene glycol structure to participate in the polycondensation reaction. The rigid ring in the furandicarboxylic acid structure can improve the high temperature resistance of the PET material, and after adding furandicarboxylic acid, the tensile strength of the material is improved, but the degree of improvement is very limited. The applicant uses the Friedel-Crafts acylation reaction, aluminum chloride as a Lewis acid catalyst, and acetic anhydride to modify an acetyl group at the ortho position of the carboxyl group on furandicarboxylic acid. On the one hand, the acetyl group is a polar group, which improves the polarity of the modified furandicarboxylic acid; on the other hand, the introduction of the acetyl group destroys the symmetry of the furandicarboxylic acid structure, further improving the polarity of the modified furandicarboxylic acid. The modified furandicarboxylic acid with higher polarity increases the bonding force between polymer chains, thereby improving the tensile strength of the PET material.

[0025] In some embodiments of the present invention, the mass ratio of furandicarboxylic acid, acetic anhydride and aluminum chloride in the step is 1:(0.6-1):(1.7-2.1).

[0026] Preferably, in the step, the mass ratio of furandicarboxylic acid, acetic anhydride and aluminum chloride is 1:0.8:1.9.

[0027] The applicant selected furandicarboxylic acid, acetic anhydride and aluminum chloride in a specific mass ratio to make the polarity of the modified furandicarboxylic acid stronger, thereby increasing the bonding force between polymer chains and thus improving the tensile strength of the PET material.

[0028] In some embodiments of the present invention, the catalyst is at least one of germanium dioxide, antimony trioxide and antimony glycolate.

[0029] Germanium dioxide, antimony trioxide and antimony glycol can increase the reaction rate of the polycondensation step and improve the production efficiency of PET materials.

[0030] In some embodiments of the present invention, the antioxidant is antioxidant 1010 or antioxidant 1076.

[0031] Antioxidant 1010 and antioxidant 1076 are often added to plastic materials, which can effectively inhibit or reduce the thermal oxidation reaction rate of PET materials and extend the service life of PET materials.

[0032] Another aspect of the present invention provides a method for preparing a high temperature resistant, oven resistant, and microwave resistant PET material, comprising the following steps:

[0033] Ⅰ. Add terephthalic acid, ethylene glycol, modified isosorbide, modified furandicarboxylic acid and a catalyst into a reaction vessel, introduce nitrogen to replace the air, stir, react at a reaction pressure of 0.22-0.35 MPa and a temperature of 242-255°C for 3-5 hours, release the pressure, evacuate, and then heat to 275-282°C and react for 2.5-3.5 hours to obtain a polycondensate;

[0034] Ⅱ. The nucleating agent, crystallization accelerator, antioxidant and the polycondensate prepared in step Ⅰ are mixed and added into an extruder for mixing, and then granulated by pulling to obtain the high temperature resistant, oven resistant and microwave resistant PET material.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The present invention utilizes terephthalic acid, ethylene glycol, modified isosorbide, modified furandicarboxylic acid, and a catalyst to prepare a polymer, and then mixes it with a nucleating agent, a crystallization accelerator, and an antioxidant before granulation to obtain a high-temperature, oven-resistant, and microwave-resistant PET material. The PET material has the advantages of good high-temperature resistance and high tensile strength, and can be used for a long time in a high-temperature environment of a microwave oven or an oven.

[0037] (2) The present invention utilizes 3-hydroxypropionic acid to modify isosorbide, which not only improves the high temperature resistance of the material, but also the hydroxyl groups in the prepared modified isosorbide structure are far away from the rigid ring with large steric hindrance, thereby improving the reaction performance of the hydroxyl group and increasing the length of the polymer molecular chain, thereby improving the tensile strength of the material.

[0038] (3) The present invention utilizes acetic anhydride and aluminum chloride to modify furandicarboxylic acid. On the one hand, the modified furandicarboxylic acid can still improve the high temperature resistance of the material when participating in the copolymerization reaction. On the other hand, the modification reaction introduces a polar group acetyl group into the ortho position of the carboxyl group on the furandicarboxylic acid structure, reduces the symmetry of furandicarboxylic acid, and increases the polarity, thereby increasing the bonding force between polymer chains and increasing the tensile strength of the material. DETAILED DESCRIPTION

[0039] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0040] In the following examples, except for modified isosorbide and modified furandicarboxylic acid, the other compound monomers and related reagents used can be purchased from the market. Among them, nano titanium dioxide was purchased from Ningbo Luofei Nanotechnology Co., Ltd.; polyethylene glycol was purchased from Shanghai Donghui Chemical Technology Co., Ltd.; polytetrahydrofuran ether glycol was purchased from Jining Huakai Resin Co., Ltd.

[0041] Preparation Example 1

[0042] The preparation method of modified isosorbide A comprises the following steps:

[0043] 0.05 g of p-toluenesulfonic acid, 2 g of isosorbide and 1.56 g of 3-hydroxypropionic acid were added to 20 ml of toluene in sequence, stirred for 15 min, refluxed at 115° C. for 6 h, and separated by column chromatography to obtain modified isosorbide A.

[0044] Preparation Example 2

[0045] The preparation method of modified isosorbide B is the same as that of modified isosorbide A, except that the mass of 3-hydroxypropionic acid added in the step is 1 g.

[0046] Preparation Example 3

[0047] The preparation method of modified furandicarboxylic acid A comprises the following steps:

[0048] 1.92 g of aluminum chloride and 1 g of furandicarboxylic acid were added to 20 ml of dichloromethane, stirred for 15 min, 0.81 g of acetic anhydride was added, reacted at 25° C. for 8 h, and separated by column chromatography to obtain modified furandicarboxylic acid A.

[0049] Preparation Example 4

[0050] The preparation method of modified furandicarboxylic acid B is the same as that of modified furandicarboxylic acid A, except that the mass of acetic anhydride added in the step is 0.4 g.

[0051] Preparation Example 5

[0052] The preparation method of modified furandicarboxylic acid C is the same as that of modified furandicarboxylic acid A, except that the mass of aluminum chloride added in the step is 1.2 g.

[0053] Example 1

[0054] A high-temperature, oven-resistant, microwave-resistant PET material comprises the following raw materials, measured by weight: 56 parts of terephthalic acid, 25 parts of ethylene glycol, 1.5 parts of a nucleating agent, 5 parts of polyethylene glycol, 19 parts of modified isosorbide A, 12 parts of modified furandicarboxylic acid A, 0.8 parts of germanium dioxide, and 0.4 parts of an antioxidant 1010.

[0055] Among them, modified isosorbide A is prepared by Preparation Example 1, and modified furandicarboxylic acid A is prepared by Preparation Example 3.

[0056] In terms of weight, the nucleating agent is a mixture of 0.8 parts of sodium o-chlorobenzoate and 0.7 parts of nano titanium dioxide.

[0057] The preparation method of the high temperature resistant, oven resistant and microwave resistant PET material in this embodiment comprises the following steps:

[0058] Ⅰ. Add terephthalic acid, ethylene glycol, modified isosorbide A, modified furandicarboxylic acid A and germanium dioxide into a reaction vessel, introduce nitrogen to replace the air, stir, react at a reaction pressure of 0.32 MPa and a temperature of 251 ° C for 4 hours, release the pressure after the reaction, evacuate to a vacuum degree of -0.095 MPa, then raise the temperature to 279 ° C, react for 3 hours to obtain a polycondensate;

[0059] Ⅱ. Sodium o-chlorobenzoate, nano titanium dioxide, polyethylene glycol, antioxidant 1010 and the polycondensate obtained in step Ⅰ are mixed and added to an extruder for mixing, followed by traction granulation to obtain the high temperature resistant, oven resistant and microwave resistant PET material.

[0060] Example 2

[0061] A high-temperature, oven-resistant, microwave-resistant PET material comprises the following raw materials, measured by weight: 54 parts of terephthalic acid, 23 parts of ethylene glycol, 1.2 parts of a nucleating agent, 4 parts of polytetramethylene glycol, 19 parts of modified isosorbide A, 12 parts of modified furandicarboxylic acid A, 0.5 parts of antimony trioxide, and 0.2 parts of an antioxidant 1076.

[0062] Among them, modified isosorbide A is prepared by Preparation Example 1, and modified furandicarboxylic acid A is prepared by Preparation Example 3.

[0063] In terms of weight, the nucleating agent is a mixture of 0.6 parts of sodium o-chlorobenzoate and 0.6 parts of nano titanium dioxide.

[0064] The preparation method of the high temperature resistant, oven resistant and microwave resistant PET material in this embodiment comprises the following steps:

[0065] Ⅰ. Add terephthalic acid, ethylene glycol, modified isosorbide A, modified furandicarboxylic acid A and antimony trioxide into a reaction vessel, introduce nitrogen to replace the air, stir, react at a reaction pressure of 0.22MPa and a temperature of 242°C for 5h, release the pressure after the reaction, evacuate to a vacuum degree of -0.095MPa, then raise the temperature to 275°C, react for 3.5h to obtain a polycondensate;

[0066] Ⅱ. Sodium o-chlorobenzoate, nano titanium dioxide, polytetramethylene glycol, antioxidant 1076 and the polycondensate obtained in step Ⅰ are mixed and added to an extruder for mixing, followed by traction granulation to obtain the high temperature resistant, oven resistant and microwave resistant PET material.

[0067] Example 3

[0068] A high-temperature, oven-resistant, microwave-resistant PET material comprises the following raw materials, measured by weight: 58 parts of terephthalic acid, 27 parts of ethylene glycol, 1.8 parts of a nucleating agent, 6 parts of polytetramethylene glycol, 19 parts of modified isosorbide A, 12 parts of modified furandicarboxylic acid A, 1 part of antimony trioxide, and 0.6 parts of an antioxidant 1076.

[0069] Among them, modified isosorbide A is prepared by Preparation Example 1, and modified furandicarboxylic acid A is prepared by Preparation Example 3.

[0070] In terms of weight, the nucleating agent is a mixture of 0.9 parts of sodium o-chlorobenzoate and 0.9 parts of nano titanium dioxide.

[0071] The preparation method of the high temperature resistant, oven resistant and microwave resistant PET material in this embodiment comprises the following steps:

[0072] Ⅰ. Add terephthalic acid, ethylene glycol, modified isosorbide A, modified furandicarboxylic acid A and antimony trioxide into a reaction vessel, introduce nitrogen to replace the air, stir, react at a reaction pressure of 0.35 MPa and a temperature of 255 ° C for 3 hours, release the pressure after the reaction, evacuate to a vacuum degree of -0.095 MPa, then raise the temperature to 282 ° C, react for 2.5 hours to obtain a polycondensate;

[0073] Ⅱ. Sodium o-chlorobenzoate, nano titanium dioxide, polytetramethylene glycol, antioxidant 1076 and the polycondensate obtained in step Ⅰ are mixed and added to an extruder for mixing, followed by traction granulation to obtain the high temperature resistant, oven resistant and microwave resistant PET material.

[0074] Example 4

[0075] A high-temperature, oven-resistant, microwave-resistant PET material comprises the following raw materials, measured by weight: 55 parts of terephthalic acid, 26 parts of ethylene glycol, 1.6 parts of a nucleating agent, 5 parts of polyethylene glycol, 17 parts of modified isosorbide A, 14 parts of modified furandicarboxylic acid A, 0.6 parts of germanium dioxide, and 0.3 parts of an antioxidant 1010.

[0076] Among them, modified isosorbide A is prepared by Preparation Example 1, and modified furandicarboxylic acid A is prepared by Preparation Example 3.

[0077] In terms of weight, the nucleating agent is a mixture of 0.8 parts of sodium o-chlorobenzoate and 0.8 parts of nano titanium dioxide.

[0078] The preparation method of the high temperature resistant, oven resistant and microwave resistant PET material in this embodiment is the same as that in Example 1.

[0079] Example 5

[0080] A high-temperature, oven-resistant, microwave-resistant PET material comprises the following raw materials, measured by weight: 57 parts of terephthalic acid, 24 parts of ethylene glycol, 1.4 parts of a nucleating agent, 5 parts of polyethylene glycol, 21 parts of modified isosorbide A, 10 parts of modified furandicarboxylic acid A, 0.7 parts of germanium dioxide, and 0.5 parts of an antioxidant 1010.

[0081] Among them, modified isosorbide A is prepared by Preparation Example 1, and modified furandicarboxylic acid A is prepared by Preparation Example 3.

[0082] In terms of weight, the nucleating agent is a mixture of 0.7 parts of sodium o-chlorobenzoate and 0.7 parts of nano titanium dioxide.

[0083] The preparation method of the high temperature resistant, oven resistant and microwave resistant PET material in this embodiment is the same as that in Example 1.

[0084] Example 6

[0085] A high-temperature, oven-resistant, microwave-resistant PET material and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that modified isosorbide A is replaced by modified isosorbide B in equal amounts, wherein modified isosorbide B is prepared by Preparation Example 2.

[0086] Example 7

[0087] A high temperature resistant, oven resistant, microwave resistant PET material and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that modified furan dicarboxylic acid B is used to replace modified furan dicarboxylic acid A in equal amounts, wherein modified furan dicarboxylic acid B is prepared by Preparation Example 4.

[0088] Example 8

[0089] A high temperature resistant, oven resistant, microwave resistant PET material and a preparation method thereof. The specific implementation manner is the same as that of Example 1, except that modified furan dicarboxylic acid C is used to replace modified furan dicarboxylic acid A in equal amounts, wherein modified furan dicarboxylic acid C is prepared by Preparation Example 5.

[0090] Comparative Example 1

[0091] A PET material and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that the modified isosorbide A is replaced by an equal amount of commercially available conventional isosorbide.

[0092] Comparative Example 2

[0093] A PET material and a preparation method thereof, wherein the specific implementation manner is the same as that of Example 1, except that the modified furandicarboxylic acid A is replaced by an equal amount of commercially available conventional furandicarboxylic acid.

[0094] Performance Testing

[0095] (1) Thermal deformation temperature

[0096] The heat deformation temperature of PET material is tested according to the test standard GB / T1643-2004.

[0097] (2) Tensile strength

[0098] The tensile strength of PET material was tested according to the test standard GB / T 1040.2-2006.

[0099] (3) Microwave resistance

[0100] After the PET pellets are melted, they are plasticized, extruded and stretched into a film using a twin-screw extruder to make a PET film with a thickness of 0.1 mm. The film is placed in a microwave oven for 100 minutes, of which 90 minutes are boiled and 10 minutes are baked to observe whether the sample has fogging, bubbling or warping. Specifically, the test results are divided into two categories: "A" and "B". "A" refers to the PET film without fogging, bubbling or warping; "B" refers to the PET film with fogging, bubbling or warping.

[0101] The heat deformation temperature, tensile strength and microwave resistance of the PET materials prepared in Examples 1-8 and Comparative Examples 1-2 were tested according to the above test methods. The test results are shown in Table 1.

[0102] Table 1

[0103] Group Heat deformation temperature(℃) Tensile strength(MPa) Microwave resistance Example 1 181.2 67.9 First Example 2 181 67.8 First Example 3 180.9 67.6 First Example 4 180.8 67.5 First Example 5 180.8 67.3 First Example 6 180.6 65.5 First Example 7 180.7 66.1 First Example 8 180.6 65.8 First Comparative Example 1 180.5 62.7 First Comparative Example 2 180.5 63.5 First

[0104] As shown in Table 1, the PET materials in Examples 1-5 of the present invention have the advantages of good high temperature resistance and microwave resistance and high tensile strength. Among them, Example 6 reduces the amount of 3-hydroxypropionic acid, which affects the process of the modification reaction, resulting in a decrease in the reactivity of the modified isosorbide hydroxyl group, shortening the polymer molecular chain, and thus reducing the tensile strength; Examples 7 and 8 respectively reduce the amount of acetic anhydride and aluminum chloride, which affects the reaction degree of the Friedel-Crafts acylation reaction, reduces the polarity of the modified furandicarboxylic acid, and leads to a decrease in the binding force between polymer chains, thereby reducing the tensile strength of the material; Comparative Example 1 uses commercially available conventional isosorbide to replace modified isosorbide, and the hydroxyl group connected to the rigid ring has poor reactivity, which reduces the molecular weight of the polymer chain, thereby reducing the tensile strength of the PET material; Comparative Example 2 uses commercially available conventional furandicarboxylic acid to replace modified furandicarboxylic acid, and the polarity of conventional furandicarboxylic acid is small, which reduces the binding force between polymer chains, thereby reducing the tensile strength of the material.

[0105] The above implementation modes are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the content of the present invention and implement it, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A high temperature resistant, oven resistant, microwave resistant PET material, characterized in that: The raw materials include the following in parts by weight: 54-58 parts of terephthalic acid, 23-27 parts of ethylene glycol, 1.2-1.8 parts of nucleating agent, 4-6 parts of crystallization accelerator, 17-21 parts of modified isosorbide, 10-14 parts of modified furandicarboxylic acid, 0.5-1 parts of catalyst, and 0.2-0.6 parts of antioxidant; The preparation method of the modified isosorbide comprises the following steps: Add p-toluenesulfonic acid, isosorbide and 3-hydroxypropionic acid to toluene in sequence, stir for 13-18 minutes, reflux at 110-115° C. for 5-6 hours, separate by column chromatography, and obtain modified isosorbide; The preparation method of the modified furandicarboxylic acid comprises the following steps: Aluminum trichloride and furandicarboxylic acid are added to dichloromethane, stirred for 12-15 minutes, acetic anhydride is added, reacted at a temperature of 21-26° C. for 7-8 hours, and separated by column chromatography to obtain modified furandicarboxylic acid.

2. The high temperature resistant, oven resistant, microwave resistant PET material according to claim 1, characterized in that: The nucleating agent is a mixture of sodium o-chlorobenzoate and nano titanium dioxide.

3. The high temperature resistant, oven resistant and microwave resistant PET material according to claim 1, characterized in that: The crystallization accelerator is polyethylene glycol or polytetramethylene glycol.

4. The high temperature resistant, oven resistant and microwave resistant PET material according to claim 1, characterized in that: The mass ratio of isosorbide to 3-hydroxypropionic acid is 1:(0.6-0.9).

5. The high temperature resistant, oven resistant, microwave resistant PET material according to claim 1, characterized in that: The mass ratio of furandicarboxylic acid, acetic anhydride and aluminum chloride is 1:(0.6-1):(1.7-2.1).

6. The high temperature resistant, oven resistant, microwave resistant PET material according to claim 1, characterized in that: The catalyst is at least one of germanium dioxide, antimony trioxide and antimony glycolate.

7. The high temperature resistant, oven resistant, microwave resistant PET material according to claim 1, characterized in that: The antioxidant is antioxidant 1010 or antioxidant 1076.

8. A method for preparing the high temperature resistant, oven resistant and microwave resistant PET material according to any one of claims 1 to 7, characterized in that: The steps include: Ⅰ. Add terephthalic acid, ethylene glycol, modified isosorbide, modified furandicarboxylic acid and a catalyst into a reaction vessel, introduce nitrogen to replace the air, stir, react at a reaction pressure of 0.22-0.35 MPa and a temperature of 242-255°C for 3-5 hours, release the pressure, evacuate, and then heat to 275-282°C and react for 2.5-3.5 hours to obtain a polycondensate; Ⅱ. The nucleating agent, crystallization accelerator, antioxidant and the polycondensate prepared in step Ⅰ are mixed and added into an extruder for mixing, and then granulated by pulling to obtain the high temperature resistant, oven resistant and microwave resistant PET material.